Response Surface Methodology: Optimisation of Antifungal Bioemulsifier from Novel Bacillus thuringiensis. (14th October 2014) - Rajendran, Deepak; Venkatachalam, Ponnusami; Ramakrishnan, Jayapradha
Abstract : An antifungal bioemulsifier compound was produced from a novel strain of Bacillus thuringiensis pak2310. To accentuate the production and as the first step to improve the yield, a central composite design (CCD) was used to study the effect of various factors like minimal salts (1X and 3X), glycerol concentration (2% and 4%), beef extract concentration (1% and 3%), and sunflower oil concentration (2% and 4%) on the production of bioemulsifier molecule and to optimize the conditions to increase the production. The E 24 emulsification index was used as the response variable as the increase in surfactant production was seen to be proportional to increased emulsification. A quadratic equation was employed to express the response variable in terms of the independent variables. Statistical tools like student's t -test, F -test, and ANOVA were employed to identify the important factors and to test the adequacy of the model. Under optimum conditions (1X concentration of minimal salts (MS), 2.6% glycerol (v/v), 1% beef extract (w/v), and 2% sunflower oil (v/v)) a 65% increase in yield was produced.